An Examination of Historical Linkages in the Evolution of Finance Theory - Eswaran, M. B. (Indian Journal of Finance, 2011)
This article attempts to trace out the historical linkages in the evolution of the (1) Portfolio Theory, (2) Efficient Market Hypothesis and (3) International Finance, the three most important strands of work in the theory of finance, by providing a history of aspects of the evolution of finance theory, emphasizing the foundation-setting contributions by key theorists over the last four centuries.